Pyogenic liver abscess following biliary stent placement in pancreatic cancer patients: a retrospective case series - Dongxue Geng; Nan Lv; Yi Miao (BMC Cancer, 2025)
Abstract Biliary stent placement is widely used in clinical, especially in patients with pancreatic cancer complicated with obstructive jaundice. Pyogenic liver abscess (PLA) is a severe complication following biliary stent placement which predominantly occurs in the right lobe of the liver, with an incidence rate ranging from 4.3% to 13.5% and a mortality rate up to 30%. It is related to the following mechanisms: retrograde bacterial infection; bile stasis and increased bile duct pH; stent-related bile duct injury; biofilm formation; immune system suppression. The main causative pathogens are gram-negative bacilli, particularly Escherichia coli and Klebsiella pneumoniae. The combination of antibiotic therapy and percutaneous transhepatic abscess drainage is the main treatment option.